Harmony of Religious Tolerance: A Case Study of Minority Islamic Communities - Hasbi Hasbi; Nursaeni Nursaeni; Nurul Aswar; Erwatul Efendi (State Islamic Institute of Palopo, 2023)
This study aims to determine the life of religious harmony in Seko District, North Luwu Regency, living in harmony, safety, peace without discrimination among religious believers. As well as knowing the factors that determine the life of harmony, harmony, peace and tolerance in the life system of the majority Christian and Muslim minority communities. Data obtained by observation, interview, and decumentation are processed qualitatively descriptively by data reduction analysis, data display and data conclusion. The results highlight that minority Muslims are able to maintain harmony and tolerance in a majority Christian society. Factors such as kinship, solidarity, and the maintenance of traditional values are the main foundations in maintaining harmonious relations between religious communities. The study also examines the contribution of religious, educational, and public policy institutions in creating an environment that supports tolerance and mutual respect. Empirical results show that well-maintained practices of harmony, solidarity, and tolerance in Seko are clear examples of successful integration. Second, identify the factors that cause harmonious religious life in Seko with a focus on kinship, the role of customary law, collaboration between parties, economic equality, and the maintenance of local identity. These results provide important insights for efforts to maintain harmony amid the complexities of multicultural societies and provide a holistic view of the importance of collaboration in building a peaceful, harmonious and tolerant environment in the region